Penerapan Green Economy dalam Pengembangan Pariwisata Halal - Fauzi, Muhamad; Wulpiah, Wulpiah; Anisa, Anisa (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
The research objective was to determine customer satisfaction in inpatient and outpatient installations; know consumer retention in inpatient and outpatient installations and; to analyse the relationship between the length of treatment again with customer satisfaction at the inpatient installation as well; analyse the relationship between the length of treatment again with customer/patient satisfaction at outpatient installations. The results showed that the level of patient satisfaction at the inpatient and outpatient installations described in the six indicators of satisfaction, the majority of which had good patient satisfaction. The results of the profitability measurement show that there is a decrease in the level of consumer profit, this condition is not good for hospital management. There was an increase in retention in outpatient and emergency departments, while hospitalization and use of operating rooms decreased. There was an increase in acquisitions in inpatient installations and the use of operating rooms while outpatient care and emergency services decreased.